Performance evaluation of lime improved lateritic soil with the addition of pulverised snail shell and sawdust ash for sustainable highway infrastructure - Fadugba, Olaolu George; Ojo, Adeyemi Amos; Oluyemi Ayibiowu, Bamitale Dorcas; Omomomi, Oladapo Jayejeje; Bodunrin, Michael (Discover Civil Engineering, 2025)
This research investigated the effects of lime, Pulverized snail shell (PSS), and sawdust ash on the mechanical proper ties of lateritic soil for soil stabilization in construction. The use of this waste materials aligns with the United Nations’ Sustainable Development Goals (SDGs), particularly Goal 12 on responsible consumption and production and Goal 9 on sustainable infrastructure development. Reusing waste materials for soil stabilization supports a circular economy approach, diverting these materials from landfills and promoting their sustainable use as valuable resources. Various tests, including maximum dry density, moisture content, unconfined compressive strength (UCS), triaxial, permeability, compressibility, and California Bearing Ratio (CBR) tests, were conducted on soil samples with different proportions of additives. The results show that the addition of additives reduced maximum dry density and increased moisture content. The sample with 6% lime and 7.5% PSS exhibited the highest UCS of 302 kPa after 28 days of curing, while the untreated sample had a UCS of 121 kPa. Triaxial tests revealed reduced cohesion and increased angle of internal friction with higher additive content. The 6% lime and 7.5% PSS sample displayed the highest shear strength of 60.6 kPa and elastic modulus of 181.8 MPa. Permeability tests demonstrated that the 6% lime and 6% sawdust ash sample had the lowest permeability (6.67 × 10–7 m/s) among the stabilized samples. The untreated soil exhibited high compressibility, whereas the 6% lime and 7.5% PSS sample exhibited the highest resistance to compression and deformation. The untreated soil had a soaked CBR value of 8%, while the 6% lime and 7.5% PSS sample achieved the highest soaked CBR value of 38%, making it suitable as a sub-base material. These findings highlight the effectiveness of lime, PSS, and sawdust ash in enhancing the mechanical properties of lateritic soil and offer valuable insights for soil stabilization in construction of Sustainable Highway Infrastructure.